Statins: targeting cardiovascular disease - Mamdoo, Farouk; Raal, Frederick J. (SA Heart Journal, 2017)
The explosion of medical knowledge and the importance and real reductions in adverse cardiovascular events with improving medical therapy has seen a surge in large trials investigating the use of HMG-CoA reductase inhibitors (statins) in the treatment of patients with cardiovascular disease since the 1990s. The established pathological role of low density lipoprotein (LDL) cholesterol and the efficacy of the lipid lowering properties of statins have ushered in an effective means of managing and preventing major adverse cardiovascular events (MACE). The purpose of this article is to review the evidence to date illustrating the benefits of statin therapy and highlight some of the key features of the landmark trials in order to gain more insight in their use in the acute coronary syndromes.